2013
DOI: 10.1007/s10640-013-9699-y
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Management and Land Use Strategies to Protect Endangered Species

Abstract: We consider an ecosystem management problem where managers can use habitat creation and predator removal to conserve an endangered species. Predator removal may become particularly important in the face of habitat loss, and ecosystem management strategies that ignore the influence of habitat are likely to be inefficient. Using a bioeconomic model, we show that the marginal impact of prey habitat on predators is a key factor in determining the substitutability or complementarity of habitat and removal controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A species can be endangered if the population of its predator or that of a competitor for its niche in the habitat grows too large. Melstrom & Horan (2014) use a numerical bioeconomic model of predator culling and habitat conservation in the case of endangered caribou in Quebec to explore the role that culling can play in conservation of a prey species. They show that the optimal mixture of the two strategies depends on the impact of increased habitat on predator productivity; culling and habitat enhancement can be complements or substitutes in producing conservation benefits, and the optimal mix of strategies is likely to change with the temporal course of the species' recovery.…”
Section: Habitat Maintenance and Incidental Harmmentioning
confidence: 99%
“…A species can be endangered if the population of its predator or that of a competitor for its niche in the habitat grows too large. Melstrom & Horan (2014) use a numerical bioeconomic model of predator culling and habitat conservation in the case of endangered caribou in Quebec to explore the role that culling can play in conservation of a prey species. They show that the optimal mixture of the two strategies depends on the impact of increased habitat on predator productivity; culling and habitat enhancement can be complements or substitutes in producing conservation benefits, and the optimal mix of strategies is likely to change with the temporal course of the species' recovery.…”
Section: Habitat Maintenance and Incidental Harmmentioning
confidence: 99%
“…Bioeconomic models that integrate economic and biophysical components are often used to show that failure to consider relevant costs and benefits in resource conservation leads to inefficient outcomes (Clark 1973;Clark and Munro 1976;Clark and Kirkwood 1986;Wilen and Brown 1986;Mesterton-Gibbons 1987, 1988Crocker and Tschirhart 1992;Brock and Xepapadeus 2002). Among other topics, these models have been used to analyze fisheries (Gordon 1954;Hilborn 1976;Sanchirico and Wilen 1999), biological invasions (Leung et al 2002;Horan and Fenichel 2007;Fenichel, Horan, and Hickling 2010;Epanchin-Niell and Hastings 2010;Homans and Horie 2011), and endangered species (Alexander 2000;Melstrom and Horan 2014). Several bioeconomic papers on the subject of endangered species examine reintroduction problems.…”
Section: Introductionmentioning
confidence: 99%
“…This was recognized early by Feder and Regev (1975), who showed that when pest control applications harm the predator of a pest, myopic decision making can actually increase pest damages. Subsequent work has investigated other situations in which the pest is a predator (Melstrom and Horan, 2014;, prey (Fenichel et al, 2010;Harper and Zilberman, 1989), competitor (Barbier, 2001;Frésard and Boncoeur, 2006) and parasite (Sims et al, 2010). 1 However, most of this research has focused on pests that generate market damages rather than those that have significant nonmarket impacts.…”
Section: Introductionmentioning
confidence: 99%